2014
DOI: 10.1007/s11418-014-0849-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of anatomy and HPTLC in characterizing species of Dioscorea (Dioscoreaceae)

Abstract: The edible tubers from different species of Dioscorea are a major source of food and nutrition for millions of people. Some of the species are medicinally important but others are toxic. The genus consists of about 630 species of almost wholly dioecious plants, many of them poorly characterized. The taxonomy of Dioscorea is confusing and identification of the species is generally problematic. There are no adequate anatomical studies available for most of the species. This study is aimed to fill this gap and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 15 publications
1
17
1
1
Order By: Relevance
“…During the anatomical study (Raman et al 2014) of various species of Dioscorea L. (Dioscoreaceae), two unusual types of raphide crystals were observed in the tubers of D. polystachya . A survey of the literature showed that they did not represent any of the four types (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the anatomical study (Raman et al 2014) of various species of Dioscorea L. (Dioscoreaceae), two unusual types of raphide crystals were observed in the tubers of D. polystachya . A survey of the literature showed that they did not represent any of the four types (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cortical cells are devoid of starch whereas the cells of the inner ground tissue are filled with large amounts of starch grains. The tubers of this species are rich in various types of raphide crystals which are concentrated in the cortex region and sparingly distributed in the ground tissue (Raman et al 2014). Type III ( Agave ) crystals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the storage organs of most root and tuber crops originate from the roots (sweet potato and cassava), stem (potato) or corm (taro), yam tubers are derived from the hypocotyl (Lawton and Lawton 1969;Shewry 2003). The tubers of Chinese yam feature a thin brown skin made of cork cells that covers the (Zhao et al 2018) inner white flesh (Raman et al 2014). Small roots on the tuber surface confer a hairy appearance (Coursey 1967a).…”
Section: Tuber Anatomy and Growthmentioning
confidence: 99%
“…Many idioblasts containing calcium oxalate embedded in mucilage are distrusted in the cortex and ground tissue. The starch grains are oval, elliptic or shell-shaped, 10–39 µm long and 7–29 µm wide (Raman et al 2014 ).…”
Section: Botanical and Physiological Propertiesmentioning
confidence: 99%
“…This genus is economically important for their tubers, which provide starch as a dietary staple as well as cortisone and other steroid hormones, such as dioscin (Aumsuwan et al, ; Cho et al, ; Jeon et al, ). However, Dioscorea species are hard to identify due to high morphological diversity, dioecy, small flowers, and morphological similarities between various species in this genus (Raman et al, ; Wilkin et al, ). Distinguishing Dioscorea species based on morphological traits is unreliable, while using DNA barcodes ( mat K, rbc L, psb A‐ trn H, trn L‐F) for Dioscorea species, identification has previously showed relatively low discrimination success, with the highest rate of 23.26% derived from use of the mat K sequences (Gao et al, ; Mukherjee & Bhat, ; Sun et al, ).…”
Section: Introductionmentioning
confidence: 99%